Drivers of Private Equity Investment in CEE and Western European Countries - Kerstin Bernoth; Roberta Colavecchio; Magdolna Sass (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
A strong private equity market is a cornerstone for commercialization and innovation in modern economies. However, substantial differences exist in the relative amounts raised and invested in private equity across European countries. We investigate the macro-determinants of private equity investment in Europe, focusing on the comparison between CEE and Western European countries. Our estimations are based on a data set running from 2001 to 2008 and covers 14 Western European and three CEE countries. Applying robust estimation techniques we identify a 'robust' set of determinants of private equity activity in both regions. We find similarities as well as differences in the driving forces of private equity investments in Western European and CEE countries. Our results suggest that commercial bank lending, equity market capitalization, unit labour costs and corporate tax rates are significant determinants of private equity activity.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: C23; C52; E22; G24; 330; Private Equity; Venture Capital; Extreme Bounds Analysis; Central and Eastern Europe